L'apocalypse des animaux (1 Hen 85-90) : une propagande militaire? : approches narrative, historico-critique, perspectives théologiques - Assefa, Daniel. (Supplements to the Journal for the Study of Judaism, 2007)
For the majority of scholars, the Animal Apocalypse is a militant text, a piece of pro-Maccabean propaganda. This text, however, develops theological reflections that are distinctly different from a justification of an armed struggle. Its themes are even incompatible with the Maccabean movement. It is impossible to condemn the Second Temple and, at the same time, mobilise people for a fight in order to purify that very Temple. After dealing with text-critical issues, this work challenges the thesis that the text is military propaganda through the use of narrative and historical approaches. The analyses, besides proposing a new way of a studying an apocalypse, spell out the peculiarity and the significance of the theology of the Animal Apocalypse in connection with the biblical history of Israel and the theology of the Qumran community.